WOMEN'S POSITION IN JOE WRIGHT'S PRIDE AND PREJUDICE MOVIE (2005): A FEMINIST APPROACH - RATRI S.P, RANI DIANING (2011)
The aim of this research is to know the women's position in Joe Wright's Pride and Prejudice movie. The objective of this study is to analyze the movie based on its structural analysis and its feminist analysis. This research is qualitative research. The object of this study is Joe Wright's Pride and Prejudice movie published in 2005 by Universal Pictures. The data sources are divided into two, namely primary and secondary data source. The primary data source is Pride and Prejudice movie directed by Joe Wright released in 2005 and secondary data source is the other sources that are the reference and material taken from book and internet related to the analysis of the movie. The method of data collecting is library research. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows that the major character has equal position in society. It means that the women's position, women's role, women's right, and women's participation are not appropriate with English society in the movie.